Antidepressant Effects of Selective Slow Wave Sleep Deprivation in Major Depression: A High-Density EEG Investigation - Landsness, Eric C. (2011)
Sleep deprivation can acutely reverse depressive symptoms in some patients with major depression. Because abnormalities in slow wave sleep are one of the most consistent biological markers of depression, it is plausible that the antidepressant effects of sleep deprivation are due to the effects on slow wave homeostasis. This study tested the prediction that selectively reducing slow waves during sleep (slow wave deprivation; SWD), without disrupting total sleep time, will lead to an acute reduction in depressive symptomatology. As part of a multi-night, cross-over design study, participants with major depression (non-medicated; n = 17) underwent baseline, SWD, and recovery sleep sessions, and were recorded with high-density EEG (hdEEG). During SWD, acoustic stimuli were played to suppress subsequent slow waves, without waking up the participant. The effects of SWD on depressive symptoms were assessed with both self-rated and researcher-administered scales. Participants experienced a significant decrease in depressive symptoms according to both self-rated (p = .007) and researcher-administered (p = .010) scales, while vigilance was unaffected. The reduction in depressive symptoms correlated with the overnight dissipation of fronto-central slow wave activity (SWA) on baseline sleep, the rebound in right frontal all-night SWA on recovery sleep, and the amount of REM sleep on the SWD night. In addition to highlighting the benefits of hdEEG in detecting regional changes in brain activity, these findings suggest that SWD may help to better understand the pathophysiology of depression and may be a useful tool for the neuromodulatory reversal of depressive symptomatology.